Digital Extension of Digital Literacy Competence for Islamic Religious Education Teachers in the Era of Digital Learning - Reksiana; Abuddin Nata; Dede Rosyada; Maila Dinia Husni Rahiem; Abdulbosit R. Rafikjon Ugli (Jurnal Pendidikan Agama Islam)
Purpose –This study aims to analyze the digital literacy competence of Islamic Education teachers at Al-Fath Cirendeu Junior High School, South Tangerang City State Junior High School 3, South Tangerang State Junior High School 6, and Darussalam Ciputat Junior High School.